Conformal Automotive Roof-Top Antenna Cavity with Increased Coverage to Vulnerable Road Users - Artner, Gerald; Kotterman, Wim; Galdo, Giovanni Del; Hein, Matthias A. (IEEE Antennas and Wireless Propagation Letters, 2018)
Cooperatively driving cars benefit from increased coverage toward driving direction for communication with vulnerable road users. Antenna cavities were designed, prototyped, and measured for integration into car roofs above the windshield. Two different antenna cavities were investigated. First, an antenna cavity made from carbon fiber reinforced polymer was measured without a vehicle, to obtain general results without model specific influence. Second, a metal cavity was built into the roof of a sedan-Type passenger car to include the marked effects of the car body and provide a proof of performance. Gain patterns were measured in anechoic chambers. Results show that the antenna structure and mounting position are suitable for omnidirectional radiation with increased radiation toward low elevation angles in driving direction.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Antenna; automotive; carbon fiber reinforced polymer (CFRP); cavity; conformal; vehicular; windshield